THE INFLUENCE OF THE MAKE A MATCH LEARNING MODEL WITH QUIZ ON THE PHYSICS LEARNING OUTCOMES OF STUDENTS IN CLASS XI MIPA SMAN 1 SIBERUT UTARA (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2022)
The learning model that is applied is a model of making quizzes with matches. The purpose of this study was to see the effect of applying the make a match quiz model to the physical learning outcomes of students in class XI MIPA SMAN 1 Siberut Utara. This type of research is a quasi-experimental research with a posttest only control group design. The population of this study were students of class XI MIPA SMAN 1 Siberut Utara. Sampling was carried out using saturated sampling. Where all the population is sampled. Class XI MIPA 1 was selected as the experimental class and class XI MIPA 2 as the control class of the study. The instrument in this study was based on a final test in the form of essays and student observation sheets during learning at each meeting. Based on the data obtained, the average learning outcomes of the cognitive domain in the experimental class are 74.41, while the control class is 66.96, and the effective assessment of students during the learning process in the experimental class is an average of 89.06 and the control class is an average of 66.92. . Furthermore, from hypothesis testing using the t test, it is obtained that t_(count )= 1.34 and t_(table )= 1.6, because t_(count) < t_(table ) then H_1 is rejected. So it can be said that there is no influence of the learning model with the physics learning outcomes of class XI MIPA SMAN 1 Siberut Utara.